A Study on the Factors Influencing Student’s Acceptance of Learning Management Systems: A Case of University of Perpetual Help System Pueblo de Panay (Global Journal of Human-Social Science, 2021)
The utilization of Learning Management System LMS has been given much emphasis especially during the COVID-19 pandemic period and has become a common phenomenon during the new normal This study examined the factors that influence LMS adoption among the students Drawing upon the model of technological acceptance TAM five factors have been identified such as facilitating conditions FC perceived enjoyment PE perceived service quality SQ perceived value PV and satisfaction SAT in successful acceptance of LMS as an observational viewpoint from the of the University of Perpetual Help System Pueblo de Panay The study used quantitative with the support of SPSS SEM multi-level linear regressions and regression analysis The study will add value to the growing figures of investigation on TAM by measuring the factors and their impact on LMS adoption
Keywords: learning management system (LMS); moodle; technology acceptance model (TAM)